Do common prothrombotic mutations influence the risk of cerebral ischaemia in patients with patent foramen ovale? - Pezzini, Alessandro; Grassi, Mario; Zotto, Elisabetta Del; Giossi, Alessia; Volonghi, Irene; Costa, Paolo; Grau, Armin; Magoni, Mauro; Padovani, Alessandro; Lichy, Christoph (Thrombosis and Haemostasis, 2009)
Conflicting results are available on the association of prothrombotic genetic abnormalities with patent foramen ovale (PFO)-related cerebral ischaemia. We comprehensively sought and identified studies of the association of both the factor V Leiden (FVG1691A mutation) and the prothrombin mutation (PTG20210A mutation) with PFO-related cerebral ischaemia and did meta-analyses to assess the evidence for such a relation. We analysed data from six eligible studies in 856 cases and 1,001 control subjects. Additional unpublished data from a new series including 463 subjects were also entered into the analysis. The PTG20210A variant was significantly associated with PFO-related stroke in comparison with both control subjects (odds ratio [OR] 3.85; 95% confidence interval [CI] 2.22 to 6.66) and non-PFO-associ ated stroke patients (OR 2.31; 95% CI 1.20 to 4.43), whereas a trend toward an association was observed for the FVG1691A mutation (OR 1.18; 95% CI 0.73 to 1.90, compared to control subjects; OR 1.14; 95% CI 0.62 to 2.09, compared to non-PFO-associated stroke patients). The status of carrier of either the FVG1691A mutation or the PTG20210A variant was associated with a risk for stroke of 1.98 (95% CI 1.38 to 2.83) and 1.62 (95% CI 1.03 to 2.57), as compared to control subjects and non-PFO-associated stroke patients, respectively. Addition of common prothrombotic genetic variants to standard initial screening may contribute to stratifying PFO-associated stroke patients at different risk of ischaemic events and targeting secondary prevention strategies.
Keywords: Patent foramen ovale; prothrombotic disorders; young; stroke